The Assessment of African Swine Fever Virus Risk to Belgium Early 2014, using the Quick and Semiquantitative Pandora Screening Protocol. Issue 1 (3rd May 2015) - Roelandt, S.; Van der Stede, Y.; D'hondt, B.; Koenen, F.
Summary: A risk assessment was organized during the early EU ASF outbreaks of early 2014 (February–April) and performed in cooperation with 15 Belgian and European experts on ASFV and its epidemiology in pigs/wild boar. African swine fever (ASF) is considered as one of the most dangerous infectious pig diseases, causing many outbreaks. Since the end of 2013 – early 2014, several outbreaks within the European Union (Lithuania, Poland, Estonia and Latvia) were reported to OIE, which prompted several risk assessments by (inter)national bodies and scientists. In this study, the open source, semiquantitative Pandora risk assessment tool was used for a quick overall screening of the risk posed by ASF to Belgium early 2014. A set of integrated risk scores was calculated within the Pandora framework. Experts scored the questions and uncertainty levels in the Pandora modules individually, after which the calculations were performed and averaged scores were used within pre‐defined risk scales to define and visualize the ASF risk to Belgium. Emergence risk was considered low (Pandora score 0.29), while disease consequences were deemed high (0.93); the resulting multiplicative overall risk of ASFV for Belgium was low (0.27). The Belgian experts tended to give lower risk scores than the European experts, especially for entry risk and trade/public opinion consequences. These risk scores are further interpreted with a due consideration of the qualitative data in the expert remarks and of other ASF risk assessments. The results are similar to more extensive and elaborate risk assessment models/procedures which may require more time and resources. The Pandora tool allows sequential updates to monitor (rates of) increasing risk and provides information for risk managers to organize targeted control.